2017
DOI: 10.22158/rhs.v2n3p262
|View full text |Cite
|
Sign up to set email alerts
|

Potential Biomarkers Selection for Bipolar Disorder Identification

Abstract: A biomarker is a measurable indicator of the severity or presence of some disease. A biomarker isanything that can be used as an indicator of a particular disease state or some other physiological state of an organism. The space Decomposition-Gradient-Regression (DGR) method has been developed (Li et al., 2012;Li et al., 2015)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…All control subjects were matched to their cases on race, branch of military service, date of birth (+/‐12 months), and date of military enlistment (+/‐12 months). Further details about the design, methods, and medical implications of the study can be found in the work of Li et al There are 56 complete subjects in the data used in this section. Among the 64 biomarkers recorded for each subject, we identified seven pairs strong correlated with absolute values of Pearson correlation coefficients over 0.7 and 50 pairs moderately correlated with absolute values of Pearson correlation coefficients over 0.40.…”
Section: Analysis Of the Bipolar Study For Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…All control subjects were matched to their cases on race, branch of military service, date of birth (+/‐12 months), and date of military enlistment (+/‐12 months). Further details about the design, methods, and medical implications of the study can be found in the work of Li et al There are 56 complete subjects in the data used in this section. Among the 64 biomarkers recorded for each subject, we identified seven pairs strong correlated with absolute values of Pearson correlation coefficients over 0.7 and 50 pairs moderately correlated with absolute values of Pearson correlation coefficients over 0.40.…”
Section: Analysis Of the Bipolar Study For Femalesmentioning
confidence: 99%
“…All control subjects were matched to their cases on race, branch of military service, date of birth (+/-12 months), and date of military enlistment (+/-12 months). Further details about the design, methods, and medical implications of the study can be found in the work of Li et al 28 There are 56 complete subjects in the data used in this section. Among the 64 biomarkers recorded for…”
Section: Data Introduction and Feature Space Decompositionmentioning
confidence: 99%